Identification of the Uric Acid Thresholds Predicting an Increased Total and Cardiovascular Mortality Over 20 Years - Virdis, Agostino; Masi, Stefano; Casiglia, Edoardo; Tikhonoff, Valerie; Cicero, Arrigo F.G.; Ungar, Andrea; Rivasi, Giulia; Salvetti, Massimo; Barbagallo, Carlo M.; Bombelli, Michele; Dell’Oro, Raffaella; Bruno, Berardino; et al. (Hypertension (Dallas, Tex. 1979), 2020)
Serum uric acid (SUA) levels discriminating across the different strata of cardiovascular risk is still unknown. By utilizing a large population-based database, we assessed the threshold of SUA that increases the risk of total mortality and cardiovascular mortality (CVM). The URRAH study (Uric Acid Right for Heart Health) is a multicentre retrospective, observational study, which collected data from several large population-based longitudinal studies in Italy and subjects recruited in the hypertension clinics of the Italian Society of Hypertension. Total mortality was defined as mortality for any cause, CVM as death due to fatal myocardial infarction, stroke, sudden cardiac death, or heart failure. A total of 22 714 subjects were included in the analysis. Multivariate Cox regression analyses identified an independent association between SUA and total mortality (hazard ratio, 1.53 [95% CI, 1.21–1.93]) or CVM (hazard ratio, 2.08 [95% CI, 1.146–2.97]; P<0.001). Cutoff values of SUA able to discriminate total mortality (4.7 mg/dL [95% CI, 4.3–5.1 mg/dL]) and CVM status (5.6 mg/dL [95% CI, 4.99–6.21 mg/dL]) were identified. The information on SUA levels provided a significant net reclassification improvement of 0.26 and of 0.27 over the Heart Score risk chart for total mortality and CVM, respectively (P<0.001). Sex-specific cutoff values for total mortality and CVM were also identified and validated. In conclusion, SUA levels increasing the risk of total mortality and CVM are significantly lower than those used for the definition of hyperuricemia in clinical practice. Our data provide evidence of a cardiovascular SUA threshold that might contribute in clinical practice to improve identification of patients at higher risk of CVM.